(untitled) - Daswani, Neil (New York, 2007)
This book serves as a great complement to the courses that make up the Stanford Center for Professional Development (SCPD) Security Certification Program. The book explains in detail how to defend against a wide range of attacks, and teaches principles of secure system design.
Keywords: Software protection,Computer security,Data encryption (Computer science),Phần mềm bảo vệ máy tính,Bảo mật máy tính,Mã hóa dữ liệu